Predictions of gyrokinetic turbulent transport in proton-boron plasmas on EHL-2 spherical torus - TAN, Muzhi; XU, Jianqiang; DU, Huarong; DONG, Jiaqi; XIE, Huasheng; WANG, Xueyun; HUANG, Xianli; WANG, Yumin; GU, Xiang; LIU, Bing; SHI, Yuejiang; LIANG, Yunfeng; et al. (Plasma science & technology, 2025)
The EHL-2 spherical torus at ENN is the next-generation experimental platform under conceptual design, aiming at realizing proton-boron (p- 11 B) thermonuclear fusion, which is an attractive pathway towards neutron-free fusion. To achieve high-performance steady-state plasma, it is extremely necessary to study the turbulence transport characteristics with high boron content in the plasma core. This study investigates the transport properties in the core internal transport barrier (ITB) region of p- 11 B plasma utilizing the gyrokinetic code GENE in view of the high ion temperature scenario of EHL-2, specifically focusing on the impact of boron fractions and plasma β on the microinstabilities and corresponding transport features. Numerical findings indicate that the inclusion of boron species effectively suppresses the trapped electron modes (TEMs) as well as promoting a transition from electromagnetic to electrostatic turbulence with increased boron fraction, which is a result of the suppression of microinstabilities by effective charge and mass. Moreover, it has been identified that the external E × B rotational shear has a notable inhibitory influence on transport, which can reduce the transport level by two to three orders of magnitude, especially at medium boron content. The suppressive effect of E × B on turbulence is weakened once the kinetic ballooning mode (KBM) is excited and the transport shows a rapid increase with β together with a reduction in zonal flow amplitude, which is consistent with previous findings. Therefore, it is strongly suggested that exploring advanced strategies for mitigating turbulent transport at high β regimes is necessary for the active control of plasma behavior regarding p- 11 B plasma-based fusion devices such as EHL-2.